How to manage a dry socket?- review of the latest treatment methods - Pacek, Laura; Wróbel, Aleksandra; Dziewulska, Aleksandra; Kiełt, Weronika; Kowalska, Klaudia; Kozłowska, Julia; Broniec, Gabriela; Kudła, Aleksandra; Wajdowicz, Barbara; Czapiewska, Rozalia (Journal of Education, Health and Sport, 2024)
Introduction Alveolar osteitis is the most common postoperative complication of tooth extraction. This medical condition has been recognized for decades, however its treatment approach is diverse with varying outcome. Aim of the study The purpose of this review is to examine and discuss contemporary methods of treating dry socket. Through a synthesis of available studies, the paper aims to identify the most beneficial methods to deal with this post-extraction complication. Materials and methods An analysis of scientific articles available in Pubmed and Google Scholar databases was conducted. The study used publications from 2017 to 2024. The search process included the use of the following keywords: “dry socket”, “alveolar osteitis”, “alveolitis sicca dolorosa”, “socket pain treatment”. Results Thirty-five articles were selected and reviewed carefully and independently by all authors. The agents used in the treatment of dry socket were classified as: remedies, drugs and medications, blood products, and technologies. Each group of agents is described with a discussion of their therapeutic efficacy. Summary Dry socket is a common dental problem. Currently, non-invasive methods of treating this complication are preferred. Modern solutions can provide quick and effective therapy. The treatment should relieve discomfort and promote tissue regeneration. Despite various methods, there is still no clear opinion on the best way to treat dry socket.